Controlling optical properties and optical bistability via an external magnetic field in a tripod-type atomic medium - Thi Huong, Hoang; Anh, Le Nguyen Mai; Thi Hoa Lai, Le; Hoa, Le Thanh; Van Phu, Nguyen; Doan Thanh, Thai; Tuan Anh, Nguyen; Minh Dong, Hoang (VNU Journal of Science: Mathematics - Physics, 2026)
We investigated control of optical bistability behavior based on the probe absorption and Kerr nonlinearity properties in a tripod-type degenerate four-level atom system under an external magnetic field. This excitation configuration can provide two transparent spectral regions on the probe absorption profile. It can be transitioned between the transparency and absorption regimes by turning on or off the magnetic field in different frequency domains. We can effortlessly transform one into two transparency windows, and vice versa, by modifying the intensity of the magnetic field. The investigations showed the enhancement of the Kerr nonlinearity around one/two-EIT windows, thereby forming one/two-channel optical bistability in these frequency regions. In addition, the coupling field intensity, the probe frequency detuning, and the atomic cooperation parameter have also significantly influenced the absorption spectrum, Kerr nonlinearity, and optical bistability. The proposed model has useful applications for storage and optical switching, and nonlinear logic gates in optical communications processing.